Hi there! With equations like this we want to get our variable on one side and and our constant on the other.
So with 2x + 3 = -7 you'd subtract the constant 3 from both sides of the equal sign to get 2x = -10, then you'd divide both sides by 2 to get x = -5. If you double check your work by replacing x in the original equation with our answer we'd find that 2(-5) + 3 = -7 is correct.
Hope you find this helpful :)
F(x)= (x+4) ^{2} -13 is the answer
<span />
Answer:
3/4
pick 1,3,5 (reds) from 1,3,5,7(odd-numbered)
Given, Customers pay $4 to enter the pumpkin patch.
And also given, customers pay $3 per pound for the pumpkins.
Given, $y be the total cost and there are x pounds of pumpkins.
The cost for pumpkin per pound = $3.
Therefore, the cost for x pound pumpkins = $(3x)
As the total cost includes the payment for entering the patch also,
So the total cost y = 3x + 4
We have got the required equation.
The equation to model the total cost is y = 3x+4.
Answer:
br=uh
Step-by-step explanation:
u need our help 4 this homework? Just do it yourself, though i would do this for 270 points.